The influence of additions on the combating stress in servicemen - Naumov, Valery (Journal of Education, Health and Sport, 2017)
Regardless of the type of armed conflict (armed incidents, antiterrorist operations, military operations, wars, etc.) and time of its passing, servicemen in these zones are constantly in a stressful condition. The constant impact of military operations stressful factors entails the emergence of pronounced negative mental states in many servicemen. Combating stress (CS), adaptive capabilities of servicemen, psychosocial characteristics of individuals predispose to addictive behavior. In the work presented the author examined various scientific outlooks as to the influence of addictions on CS peculiarities among servicemen, taking part in armed conflicts. It has been revealed that the features of the basic life support systems functioning in servicemen under combat conditions are subjects to significant changes in the state of health, up to pathological. The author’s primary focus is on the prognostication of the probable mental disorders, the degree of CS influence on the formation of addictions among servicemen and identification of their main markers. The content analysis of the present time existing research articles allowed the author to conclude that against the background of the CS impact risk of emergence and the process of forming additions acquires an accelerated character. This indicates the need to develop an effective system of primary and secondary prevention of the occurrence of the negative phenomena mentioned among servicemen.